Flora of the canga of the Serra dos Carajás, Pará, Brazil: Humiriaceae - Carvalho, Fernanda Antunes; Holanda, Ana Sofia Sousa de (Rodriguesia, 2018)
This study brings detailed descriptions, illustrations and comments on the morphology of Sacoglottis guianensis and Sacoglottis mattogrossensis, the only representatives of Humiriaceae occurring in the canga of Serra dos Carajás, Pará state. Sacoglottis guianensis is widely distributed in South America while S. mattogrossensis occurs in the Southern Amazon and Atlantic Forest extending southward to São Paulo. In Carajás, both species are found in the canga and transitional areas between open canga and the rainforest. © 2018 Instituto de Pesquisas Jardim Botanico do Rio de Janeiro. All rights reserved.
Flora das cangas da Serra dos Carajás, Pará, Brasil: Humiriaceae